Does Dietary Adequacy Reflect the Cognitive Performance of Children? A Study among the Homeless Children in Klang Valley, Malaysia - Chin , K.J.; A, Asma’; Yusof , HM; Churak, P.; K, Latiffah (IIUM Medical Journal Malaysia, 2020)
Introduction: Homeless children are prone to inadequate energy and nutrient intake which may highly influence their cognitive performance. However, few studies have been done in assessing diet adequacy and cognitive performance among homeless children in Malaysia. Materials and Methods: This cross-sectional study aims to assess the dietary adequacy and cognitive performance of 120 homeless children age 7-12 years living in Klang Valley. The dietary adequacy of these homeless children was assessed through two days of 24 hours of dietary recall. Dietary adequacy achievement was determined by fulfilling at least 50% of Recommended Nutrients Intake (RNI). Raven’s Coloured Progressive Matrices (RCPM) test was used to assess their cognitive performance. Results: The homeless children had an adequate intake of energy, iron, zinc, and vitamin B12. Seventy percent of homeless children had a poor cognitive performance. This study shows that there was no association between energy, iron, and vitamin B12 adequacy with cognitive performance, whereas there was a significant (p=0.028) association between zinc adequacy and children’s cognitive performance. Conclusion: These findings provide solid evidence-based for dietary adequacy and cognitive performance of the homeless children in Klang Valley. It is clear from the findings that both dietary intake and cognitive of these children require improvement for a better quality of life in the future. This study suggests that dietary adequacy does not relatively reflect the cognitive performance of these homeless children in Malaysia.